Electrically Stimulated Tunable Drug Delivery From Polypyrrole-Coated Polyvinylidene Fluoride - Miar, Solaleh; Ong, Joo L.; Bizios, Rena; Guda, Teja (Frontiers in Chemistry, 2021)
Electrical stimulus-responsive drug delivery from conducting polymers such as polypyrrole (PPy) has been limited by lack of versatile polymerization techniques and limitations in drug-loading strategies. In the present study, we report an in-situ chemical polymerization technique for incorporation of biotin, as the doping agent, to establish electrosensitive drug release from PPy-coated substrates. Aligned electrospun polyvinylidene fluoride (PVDF) fibers were used as a substrate for the PPy-coating and basic fibroblast growth factor and nerve growth factor were the model growth factors demonstrated for potential applications in musculoskeletal tissue regeneration. It was observed that 18-hours of continuous polymerization produced an optimal coating of PPy on the surface of the PVDF electrospun fibers with significantly increased hydrophilicity and no substantial changes observed in fiber orientation or individual fiber thickness. This PPy-PVDF system was used as the platform for loading the aforementioned growth factors, using streptavidin as the drug-complex carrier. The release profile of incorporated biotinylated growth factors exhibited electrosensitive release behavior while the PPy-PVDF complex proved stable for a period of 14 days and suitable as a stimulus responsive drug delivery depot. Critically, the growth factors retained bioactivity after release. In conclusion, the present study established a systematic methodology to prepare PPy coated systems with electrosensitive drug release capabilities which can potentially be used to encourage targeted tissue regeneration and other biomedical applications.